KUALITAS FISIK ORGANOLEPTIS, HARDNESS DAN KADAR AIR PADA BERBAGAI PAKAN TERNAK BENTUK PELLET - B. Sulistiyanto; R. D. Rahmawati; Cahya Setya Utama (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
This study aims to evaluate the organoleptic quality, hardness and the moisture content of various pelleted animal feeds. This research was uses descriptive method. The pellet feed used was 8 types of pellet feed from various types of livestock, namely; pellet feed for laying hens grower; starter broiler pellet feed; beef pellet feed; dairy cow feed pellets; horse pellet feed; pellet feed of laying ducks; pellet feed for fattening pigs and pellet for fattening sheep are obtained from various animal feed stalls in Central Java. The parameters observed were organoleptic, hardness and moisture content. The results showed that the organoleptic physical test, hardness and moisture content greatly affected the quality of the pellets, but the color of the pellets tended to have no difference. The conclusion of this research was that testing the quality of pellets in various livestock can be done physically, organoleptically, hardness and moisture content.